Readiness-to-change as a moderator of a web-based brief intervention for marijuana among students identified by health center screening. (1st April 2016) - Palfai, T.P.; Tahaney, K.; Winter, M.; Saitz, R.
Highlights: Readiness to change moderated the influence of a web-based brief intervention for marijuana delivered to students in a student health center. The intervention showed evidence of efficacy (compared to control) among those who were taking steps toward changing their marijuana use. The problem recognition component of readiness-to-change, however, did not significantly moderate the efficacy of the intervention Findings suggest that the eCHECKUPTOGO intervention may be most helpful for those who have initiated change in their marijuana use behavior. Abstract: Introduction: Electronic screening and brief intervention has been identified as a low cost strategy to address marijuana use among students, however there is little known about who may be most responsive to this intervention approach. This study examined whether readiness-to-change moderated the influence of a web-based intervention on frequency of use at 3-month outcomes. Methods: One-hundred twenty-three students who smoked marijuana at least monthly were identified by screening in a student health center. Baseline and 3-month outcome assessments were conducted on-line. Participants were randomly assigned to either eCHECKUP TO GO-marijuana or a control condition after completing marijuana measures and the Readiness-to-Change Questionnaire (RTCQ). Negative binomial regression analyses were conducted to examine whether the effect of the intervention on marijuana use at 3-month outcomes was moderated by the Action and Problem Recognition dimensions of the RTCQ, adjusting for baseline use. Results: Analyses showed a significant Intervention × Action interaction. Probing of interaction effects showed that among those with high scores on the Action scale participants in the intervention group reported significantly fewer days of use than those in the control condition at follow-up (IRR = 0.53, 95%CI: 0.94, 2.08). The Problem Recognition dimension did not moderate the influence of the intervention on outcomes. Conclusion: These results suggest that this eSBI may bolster change efforts among students who have begun taking steps toward changing their marijuana use.